OFR-33-77 Improved Mineral Excavation Nozzle Design Study - Summary - P. D. Lohn (The National Institute for Occupational Safety and Health (NIOSH), 1976)
The objective of this program was to develop nozzle designs to maximize the effective cutting length of a water jet. The results of the theoretical program directly support the Bureau of Mines Borehole Mining Program and their experimental program to improve the rock cutting capability of water jets. The borehole geometry requires turning the flow by 90 degrees and accelerating through the nozzle within a restricted length. Several suggestions for turning the flow are offered. The borehole space limitations constrain nozzle length, to the extent that a standard 13-degree tapered nozzle (6-1/2 degrees half angle) is too long to fit in the borehole, at production flow conditions. The design technique developed is computationally economical and enables examination of a large number of shapes and flow conditions. The nozzle design is based on design criteria of minimization of boundary layer thickness at the nozzle exit and minimization of the possibility of separation and cavitation. Six flow conditions, including pressures to 4500 psi and flow rates to 400 gpm, were examined, Best shapes were determined for all flow conditions. The best shape for a borehole reining application consists of an initial 4th degree polynominal (quartic) at the entrance followed by a straight section with a twenty degree (half-angle) taper at the exit.